Peran Program Asistensi Mengajar dalam Mendukung Kegiatan Pembelajaran Siswa Kelas IV di MIS Fathul Iman Palangka Raya - Deni Adi Saputra; Sulistiyowati Sulistiyowati; Sellawati Dewi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This study aims to examine the role of the teaching assistance program in supporting grade IV student learning at MIS Fathul Iman Palangka Raya. Basic education, especially at the fourth grade level, plays an important role in the formation of students' cognitive, affective and psychomotor foundations. However, challenges in the implementation of learning, such as limited teaching staff, variations in student abilities, and limited time for individualized guidance, often hinder the achievement of effective learning. One of the proposed solutions is a teaching assistance program, where education students assist teachers in managing the classroom and give more attention to students who need additional guidance. This research reveals that teaching assistance can positively impact the learning process by creating a more interactive, inclusive and supportive learning environment for diverse students. It assists teachers in delivering materials, providing additional explanations and managing the classroom more effectively. In addition, the program also provides opportunities for students with different abilities to get the attention they need. Based on the results of the study, the teaching assistance program proved to be effective in improving the quality of learning and supporting students' optimal development.